Integrated Characterization of MicroRNA and mRNA Transcriptome in Papillary Thyroid Carcinoma - Mohamad Yusof, Azliana; Jamal, Rahman; Muhammad, Rohaizak; Abdullah Suhaimi, Shahrun Niza; Mohamed Rose, Isa; Saidin, Sazuita; Ab Mutalib, Nurul-Syakima (Frontiers in Endocrinology, 2018)
The incidence rate of papillary thyroid carcinoma (PTC) has rapidly increased in the recent decades, and the microRNA is one of the potential biomarkers in this cancer. Despite good prognosis, certain features such as lymph node metastasis and BRAF V600E mutation are associated with a poor outcome. More than 50% of PTC patients present with lymph node metastasis and BRAF V600E is the most common mutation identified in this cancer. The molecular mechanisms underlying these features are yet to be elucidated. This study aims to elucidate miRNA-genes interaction networks in PTC with or without lymph node metastasis and to determine the association of BRAF V600E mutation with miRNAs and genes expression profiles. Next generation sequencing was performed to characterize microRNA and gene expression profiles in 20 fresh frozen tumour and the normal adjacent tissues of PTC with lymph node metastasis (LNM) positive (PTC LNM-P) and PTC without LNM (PTC LNN). BRAF V600E was genotyped using Sanger sequencing. Bioinformatics integration and pathway analysis were performed to determine the regulatory networks involved. Based on network analysis, we then investigated the association between microRNA and gene biomarkers, and pathway enrichment analysis was performed to study the role of candidate biomarkers. We identified 138 and 43 significantly deregulated microRNAs (adjusted p value < 0.05; log2 fold change ≤ -1.0 or ≥ 1.0) in PTC LNM-P and PTC LNN compared to adjacent normal tissues, respectively. Ninety-six miRNAs had significant expression ratios of 3p-to-5p in PTC LNM-P as compared to PTC LNN. In addition, ribosomal RNA-reduced RNA sequencing analysis revealed 699 significantly deregulated genes in PTC LNM-P versus normal adjacent tissues, 1362 genes in PTC LNN versus normal adjacent tissue and 1576 genes in PTC LNM-P versus PTC LNN. We provide the evidence of microRNA and gene interactions which are involved in lymph node metastasis of papillary thyroid cancer. These findings may lead to better understanding of carcinogenesis and metastasis processes. This study also complements the existing knowledge about deregulated microRNAs in papillary thyroid carcinoma development.